Floral morphology and seed yield in two Indigofera spp. as affected by shoot clipping (Journal of the Bangladesh Agricultural University, 2014)
An experiment was carried out to know the effect of shoot clipping on floral morphology and seed yield in two Indigofera spp. viz. I. tinctoria L. and I. suffruticosa Mill. All parts of shoot including the main stem were clipped at 60 cm height from the base at 120 days after sowing (DAS). At 120 DAS, I. tinctoria already exhibited 1st flowering while I. suffruticosa showed no flowering. Shoot clipping had significant effect on almost all floral morphological features in two Indigofera spp. Flower raceme?1 and pod raceme?1 were fewer in clipped plant than in unclipped one. Shoot clipping altered the size of different floral parts to a great extent. The seed yield was decreased in clipped plant than that of unclipped one. Shoot clipping decreased flower and pod size and seed yield in two Indigofera spp. DOI: http://dx.doi.org/10.3329/jbau.v11i1.18214 J. Bangladesh Agril. Univ. 11(1): 61-66, 2013